Growth and Instability in Production and Export of Indian Lac - Pal, Govind (Indian Forester, 2010)
The study to examine the growth and instability in production and export of Indian lac is based on secondary data collected for 38 years spanning from 1970-71 to 2007-08. The data were analyzed by using exponential function and instability index. During the overall period production of Indian lac registered a declining trend while, the period 2000-01 to 2007-08 was comparatively better with positive growth rate and lower instability than the past three decades of lac production in India. The export quantity also registered a declining trend during overall period while, total export value and upit value of export registered positive and significant trend. Instability was more in total export value aud unit value of export in comparison to export quantity. Instability during the period 2000-01 to 2007-08 was comparatively lower than the past three decades and overall period in quantity, total value and unit value of export. The study has emphasized on the need of intensification of efforts and exploitation of untapped potential area for increasing lac production, quality consciousness and more R & D support for improving the production and export scenario of Indian lac.